(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Food labelling plays a crucial role in promoting sustainable consumer behaviour by providing essential information on product origins, environmental impact, and ethical standards. This study aims to evaluate the influence of food labelling on consumer purchasing decisions and sustainability awareness in Latvia. A comparative analysis and synthesis of secondary data sources, including academic literature, policy documents, and market surveys, were conducted. Findings show that while food labels enhance product credibility and consumer trust, there remains a significant gap between awareness and actual purchasing behaviour. Barriers such as label complexity, higher prices, and inconsistent regulatory enforcement reduce the effectiveness of sustainability labels. These insights highlight key factors shaping consumer trust in food labelling and offer recommendations for improving sustainable consumption practices in Latvia.